The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1984
DOI: 10.1002/jsfa.2740350309
|View full text |Cite
|
Sign up to set email alerts
|

Compositional changes in chlorophylls and carotenoids during the four flushes of tea in North East India

Abstract: The quantitative changes of two pigments, chlorophylls a and b, and four major carotenoids, @-carotene, lutein, violaxanthine and neoxanthine, were investigated during four flushes of North East Indian plain teas from a deep skiffed area between April and October 1982. The tea flushes with different genetic properties were taken fromn from various Tocklai-released clones: TV-1 (Cwnellia sinensis (L.) 0. Kuntze), TV-2 (C. assamica (Masters) Wight), TV-9 (C. assarnica 'Cambod') and TV-17 (C. sinensis, hybrid). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…4 Carotenoid is also the structural and functional component of the chloroplast, with a potential positive influence on the aroma quality of black tea. 5 Pigments in tea leaves vary in amount and proportion with tea species, 6,7 ecological environments, 8,9 cultivation measures, 10,11 and tea processing methods. 12−15 In China, green tea processing generally follows the procedures of withering, de-enzyming, rolling, and drying.…”
Section: Introductionmentioning
confidence: 99%
“…4 Carotenoid is also the structural and functional component of the chloroplast, with a potential positive influence on the aroma quality of black tea. 5 Pigments in tea leaves vary in amount and proportion with tea species, 6,7 ecological environments, 8,9 cultivation measures, 10,11 and tea processing methods. 12−15 In China, green tea processing generally follows the procedures of withering, de-enzyming, rolling, and drying.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Assam type cultivars contain higher amount of polyphenols [ 2 ]. China variety cultivars generally possess quercetin and kaemferol-3-glucosides but these are totally absent or present only in traces in Assam variety [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 A. Because the tea industry in India was established and developed by the British who have heavy tastes, annual production of more than 950,000 tons of Indian tea is almost entirely black tea to meet the western people’s tastes [ 101 ]. In the Alibaba website (Alibaba.com), 2379 messages about Indian tea, including 78 products of Darjeeling black tea, were found.…”
Section: Top-grade Black Teas Worldwidementioning
confidence: 99%